2021
DOI: 10.21203/rs.3.rs-144452/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The combined healthy lifestyle score is a protective factor for cardiovascular disease: a representative national cohort study in Taiwan

Abstract: BackgroundThe protective effect of different healthy lifestyle scores for the risk of cardiovascular disease (CVD) was reported but the comparisons of performance were lack. We compared the performance measures of cardiovascular diseases from different healthy lifestyle scores among adult Taiwan.MethodsWe conducted a nationwide prospective cohort study of 6042 participants (median age 43 years, 50.2% women) in Taiwan’s Hypertensive, Hyperglycemia and Hyperlipidemia Survey, 2002 who were free of CVD at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Additionally, the study of LS7 indicates that individuals with higher score on all seven metrics had a lower risk of CVD [ 19 ]. Similarly, it has been also found that improvement in these indices over time was associated with a lower risk of CVD in the future [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the study of LS7 indicates that individuals with higher score on all seven metrics had a lower risk of CVD [ 19 ]. Similarly, it has been also found that improvement in these indices over time was associated with a lower risk of CVD in the future [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most influential variables are modifiable factors which confirm the impact of lifestyle features in the HRQoL level measured by validated questionnaires [ 2 ]. Moreover, healthy lifestyle scores are significantly correlated with CVD risk of death and they are considered as an interesting tool in health promotion [ 15 , 56 , 62 ] Similarly, some authors have suggested that the combination of different lifestyle factors may improve the predictor accuracy of the risk of non-communicable diseases 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation